THE PRACTICE OF SUBSTITUTE HEIRS IN INDONESIAN RELIGIOUS COURT: Restricted Interpretation - Mu’in, Fathul; Faisal, Faisal; Fikri, Arif; Asnawi, Habib Shulton; Nawawi, M Anwar (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
As part of reformation outcomes, the substitute heir in Islamic inheritance law has been long heeded by Indonesian jurists. However, amidst the facet of the traditional scheme, Indonesian Religious Court judges (judex factie) have not shared the same implementation of this succession. This article endeavors to examine the practice of substitute heir in the field. Relies on the Religious Court decisions as the primary source, this article argues that the norm of substitute heir (Article 185 of The Compilation of Islamic Law) has been implemented restrictedly according to The Compilation and the Supreme Court consensus. Restricted interpretation means the descendants of the pre-deceased side-relative was not accounted as substitute heir. It implies that the state reformation attempt in Islamic inheritance law has not come into play in the way the state desires.[Sebagai bagian dari hasil reformasi, substitute heir dalam hukum waris Islam telah lama diperhatikan oleh para ahli hukum Indonesia. Namun, di tengah sisi skema tradisional, hakim Pengadilan Agama Indonesia (judex factie) belum memiliki kesamaan pelaksanaan suksesi ini. Artikel ini mencoba mengkaji praktek penerapan substitute heir di lapangan. Berpijak pada putusan Pengadilan Agama sebagai sumber data utama, artikel ini berargumen bahwa norma ahli waris pengganti (Pasal 185 Kompilasi Hukum Islam) telah dilaksanakan secara terbatas menurut Kompilasi dan konsensus Mahkamah Agung. Penafsiran terbatas berarti keturunan dari kerabat menyamping yang telah meninggal dunia terlebih dahulu tidak diperhitungkan sebagai ahli waris pengganti. Ini menyiratkan bahwa upaya reformasi negara dalam hukum waris Islam belum diterapkan sesuai yang diinginkan negara.]